THE EFFECT OF SULFURIC ACID CONCENTRATION ON NICKEL RECOVERY FROM LATERITE ORE BY USING ATMOSPHERIC ACID LEACHING METHOD - Althafa Muntaqin; Lutfiah Rahmasari; Ninik Lintang Edi Wahyuni; Rony Pasonang Sihombing (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
The processing of laterite ore by pyrometallurgy requires high temperatures whereas the Atmospheric Acid Leaching (AAL) method can be performed below 100 ℃ although its nickel recovery is inconsistent. This research aims to determine the effect of sulfuric acid concentration on nickel recovery and to determine nickel recovery after extract purification by precipitation of non-nickel metals. AAL was performed with an operating temperature of 95 °C, an operating time of 5 hours, an ore-to-solvent ratio of 0.05 g/ml, a particle size of ± 200 mesh, and sulfuric acid concentration variation of 0.2–1 M. Iron precipitation was completed with a pH variation of 0.5–3.8 by the addition of ammonia. The result showed that the concentration of sulfuric acid increased nickel recovery. The nickel recovery reached 96.43% at a concentration of sulfuric acid of 1 M. Furthermore, after extract purification, nickel recovery reached 50.61%, which was achieved at an optimum pH of 3.2.